Postpartum psychosis as a presentation of panhypopituitarism - Jananee Muralidharan; Rose Tom; Jyothi Idiculla (Wolters Kluwer Medknow Publications, 2024)
We describe a young patient diagnosed with postpartum psychosis, and managed with antipsychotics. She presented with hyponatremia after an episode of gastroenteritis. Further probing revealed a history of amenorrhea after the delivery. Workup showed panhypopituitarism. This treatable cause can mimic postpartum psychosis.